Gypsum application, soil fertility and cotton root growth - Pivetta, Laercio Augusto; Castoldi, Gustavo; Pivetta, Laerte Gustavo; Mendonca Maia, Suelen Cristina; Rosolem, Ciro Antonio [UNESP] (Inst Agronomico, 2019)
Since there is no consensus on phosphogypsum (PG) rates to be used in agriculture, a better understanding of its effects on the soil solution is needed. Cotton root growth was evaluated as related to Al and Ca activity in soil solution affected by PG. The experiment was carried out in rhizotrons filled with 30.dm(-3) of soil. PG rates were estimated by multiplying the soil clay content by 0.0,1.5, 3.0, 6.0 and 12.0, and it was mixed to the sub-soil. In the upper soil layer, limestone was applied. After 90 days, samples were taken for analysis, and cotton was planted. After 27 days, plants were harvested. PG increased soil pH and decreased Al content and activity. Without PG, dissolved organic carbon concentration was high in the soil solution, which explains the predominance of carbon Al-complexed with PG application. From 1,680 kg.ha(-1) of PG (corresponding to 6 x clay content), sulphur and calcium had the highest concentrations, increasing the SO4 Al-complexed. Cotton root length decreased in the upper layer and increased in the subsoil up to 2,324 kg.ha(-1) (corresponding to 8.3 x clay content) of PG. Cotton root growth is better related with soil properties than with soil solution attributes, and the present recommendations for PG use based on soil clay content underestimate the rate to be applied.
Keywords: aluminum; dissolved organic carbon; soil chemistry